Cross-cultural development and psychometric evaluation of a measure to assess fear of childbirth prior to pregnancy - Stoll, K.; Hauck, Yvonne; Downe, S.; Edmonds, J.; Gross, M.; Malott, A.; McNiven, P.; Swift, E.; Thomson, G.; Hall, W. (Elsevier Ltd, 2015)
© 2016. Background: Assessment of childbirth fear, in advance of pregnancy, and early identification of modifiable factors contributing to fear can inform public health initiatives and/or school-based educational programming for the next generation of maternity care consumers. We developed and evaluated a short fear of birth scale that incorporates the most common dimensions of fear reported by men and women prior to pregnancy, fear of: labour pain, being out of control and unable to cope with labour and birth, complications, and irreversible physical damage. Methods: University students in six countries (Australia, Canada, England, Germany, Iceland, and the United States, n = 2240) participated in an online survey to assess their fears and attitudes about birth. We report internal consistency reliability, corrected-item-to-total correlations, factor loadings and convergent and discriminant validity of the new scale. Results: The Childbirth Fear - Prior to Pregnancy (CFPP) scale showed high internal consistency across samples (a > 0.86). All corrected-item-to total correlations exceeded 0.45, supporting the uni-dimensionality of the scale. Construct validity of the CFPP was supported by a high correlation between the new scale and a two-item visual analogue scale that measures fear of birth (r > 0.6 across samples). Weak correlations of the CFPP with scores on measures that assess related psychological states (anxiety, depression and stress) support the discriminant validity of the scale. Conclusion: The CFPP is a short, reliable and valid measure of childbirth fear among young women and men in six countries who plan to have children.